2021
DOI: 10.1515/biol-2021-0076
|View full text |Cite
|
Sign up to set email alerts
|

Primary localized cutaneous nodular amyloidosis presenting as lymphatic malformation: A case report

Abstract: Primary skin amyloidosis is a chronic skin disease in which amyloid deposits in the normal skin tissues without involving other organs. At present, the causes and mechanisms of morbidity have not been fully elucidated. There are few clinical reports of nodular skin amyloidosis, and the domestic reports are mostly limited cases. This study reported a rare case of a 46-year-old woman with primary localized cutaneous nodular amyloidosis (PLCNA). The patient presented with features of lymphatic malformation, a ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…It mainly occurs between the ages of 40 and 60, and there is no gender difference [12,15]. It is found more frequently among Asians, South Americans, and Middle Easterners [12]. Histopathological features of the nodules of both of our patients were also similar to those observed in cutaneous amyloidomas.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It mainly occurs between the ages of 40 and 60, and there is no gender difference [12,15]. It is found more frequently among Asians, South Americans, and Middle Easterners [12]. Histopathological features of the nodules of both of our patients were also similar to those observed in cutaneous amyloidomas.…”
Section: Discussionsupporting
confidence: 75%
“…Cutaneous amyloidoma usually presents clinically as single or multiple pink to brown nodules or plaques affecting predominantly the skin of the face, extremities, and genitals [12][13][14]. It mainly occurs between the ages of 40 and 60, and there is no gender difference [12,15]. It is found more frequently among Asians, South Americans, and Middle Easterners [12].…”
Section: Discussionmentioning
confidence: 99%
“…PLCNA manifests as single or multiple waxy, firm, pink, yellowish, or purplish plaques or nodules ( Figure 1 ). Atypical presentations mimicking lymphatic malformation, milia, or bullous disease have also been reported [ 12 , 13 , 14 ]. PLCNA lesions are most commonly found on the acral region, head and neck, and extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Nodular amyloidosis, derived from immunoglobulin light chains (amyloidosis light chain proteins) produced by plasma cells infiltrating the skin without associated plasma cell dyscrasia, is the least frequent subtype with only 60 cases reported. 1 , 2 Literature suggests possible associations between primary cutaneous nodular amyloidosis (PCNA), autoimmune disease, and trauma. 2 , 3 Stigall et al reported an association between infection and PCNA.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Literature suggests possible associations between primary cutaneous nodular amyloidosis (PCNA), autoimmune disease, and trauma. 2 , 3 Stigall et al reported an association between infection and PCNA. 3 Herein, we report the second case of PCNA associated with an infection, specifically Helicobacter pylori .…”
Section: Introductionmentioning
confidence: 99%